Words, deeds, and outcomes: A survey on the growth effects of exchange rate regimes - Philipp Harms; Marco Kretschmann (Swiss National Bank, Study Center Gerzensee, 2007)
Recent studies on the growth effects of exchange rate regimes offer a wide range of different, sometimes contradictory results. In this paper, we systematically compare three prominent contributions in this field. Using a common data set, a common specification, and common estimation methods, we argue that the contradictory findings can be explained by the fact that these studies use regime classifications which reflect fundamentally different aspects of exchange rate policy.
Keywords: E52; F31; F41; F43; 330; Exchange rate regimes; economic growth; monetary policy; Wechselkurssystem; Wechselkurspolitik; Wirtschaftswachstum; Schätzung; Welt